Nutritional Status of Children on Complementary Feeding in Bosomtwe-Atwima-Kwanwoma District of Ghana - Afriyie-Nkrumah, A.; Commey, V.; Adusei, A.K. (Pakistan Journal of Nutrition, 2016)
The study sought to assess the nutritional status of children on complementary feeding in relation to the practice adopted. Purposive sampling method was used in selecting respondents for the study since the work technically cover children on complementary feeding and their mothers. A sample size of 100 mothers and their children was selected which ensured that the characteristics to be studied in the population were fairly distributed. With respect to complementary feeding practices, the study revealed that the ages at which mothers introduced their children to complementary food ranges from as early as five weeks to as late as eleven months. Mothers observe hygienic practices like washing of utensils with soap and sponge before use, use of clean water and washing hands with soap before meal preparation and feeding the children. Majority of mothers (90%) personally feed their children and 84% still breast-feed their children. It was further revealed that majority of mothers (46%) do not give their children snacks with the remaining (54%) giving snacks like biscuits, pastries, banana, pawpaw and oranges to their children. The study revealed that although the health personnel are few, they were doing their best under difficult conditions such as low educational levels of the mothers, reflected in non-compliance with complementary feeding practices taught and financial constraints. These have contributed to the poor nutritional status (33% underweight, 10% wasted, 14% stunted) of most children on complementary feeding in both hospitals. Therefore, there is an urgent need to address these issues in order to make the program a success. Furthermore, regular workshops should be organized for the health personnel on the program in order to up-grade their knowledge and be abreast with current nutrition information.